2015
DOI: 10.1149/2.0181507jes
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Electrolyte Additive Mixtures for Li-Ion Cells that Promote Long Lifetime and Less Reactivity with Charged Electrodes at Elevated Temperatures

Abstract: (NMC111)/graphite and Li [Ni 0.42 Mn 0.42 Co 0.16 ]O 2 (NMC442)/graphite pouch cells demonstrate superb performance when ternary blends of electrolyte additives are added to the cells. These ternary blends contain one of vinylene carbonate (VC) or prop-1-ene-1,3-sultone (PES) plus a sulfur containing molecule and tris(trimethylsilyl) phosphite (TTSPi). Here, the excellent charge-discharge capacity retention of cells containing these ternary blends of additives is demonstrated at both 45 • C and 55 • C by comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
55
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 27 publications
0
55
0
1
Order By: Relevance
“…[18][19][20] The additive triallyl phosphate (TAP) is reported to improve the high-voltage performance.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] The additive triallyl phosphate (TAP) is reported to improve the high-voltage performance.…”
Section: 2mentioning
confidence: 99%
“…[15][16][17] Ternary additives of 2% propene sultone (PES), 1% ethylene sulfate (DTD) and 1% tris(-trimethylsilyl)-phosphite (TTSPi) (called PES211) improved the cycle and calendar life of NMC/graphite Li-ion cells under normal (i.e., 4.2 V) and high voltage (i.e., 4.4 V) operation. [18][19][20] The additive triallyl phosphate (TAP) is reported to improve the high-voltage performance. 21 Many electrolyte additives have been proposed and shown in the literature to improve cell performance and lifetime.…”
mentioning
confidence: 99%
“…By adding just a few weight percent of the right compounds to the electrolyte solution before cells are filled, one can significantly improve charge-discharge cycling performance, extend calendar lifetime, decrease detrimental gas formation, and improve lithium-ion cell safety. [1][2][3][4][5] This move to electrolyte additives has the rather practical aspect that the battery industry can tweak performance with minimal changes to their existing supply chains for LiPF 6 and solvents.1 This article will focus on Li(Ni a Mn b Co 1−a−b )O 2 (NMC)/graphite cells, for which vinylene carbonate (VC), [6][7][8][9][10] prop-1-ene-1,3-sultone (PES), [8][9][10][11][12][13][14][15] methylene methane disulfonate (MMDS), tris(trimethylsilyl) phosphite (TTSPi), 16,17 and triallyl phosphate (TAP) 18,19 are among the best reported additives. Recently, Nie et al introduced a series of Lewis acid-base adducts that may be used individually or as part of an additive blend.…”
mentioning
confidence: 99%
“…In another publication, 14 they found that the introduction of 1% VC to the methoxyethyl methyl sulfone system could provide similar cycling performance to 1.0 M LiPF 6 /EC:DMC (1:1 by volume) in LiCoO 2 /graphite full cells cycled between 3.0 to 4.2 V. Abouimrane et al 6 demonstrated that tetramethylsulfone can be used with EMC as a co-solvent and LiPF 6 Recently, our group has begun studying the effect of electrolyte additives and different solvents in Li[Ni 0.42 Mn 0.42 Co 0. 16 ]O 2 (NMC442)/graphite pouch cells which are balanced for 4.7 V. [16][17][18][19] Ma et al 16 found that NMC442/graphite pouch cells with 2% VC added to 1 M LiPF 6 EC:EMC showed dramatic impedance growth when cycled to 4.3 V and above. The addition of 2% prop-1-ene-1,3-sultone (PES) or 2% PES +1% methylene methanedisulfonate (MMDS) +1% tris(trimethylsilyl) phosphite (TTSPi) ("PES-211") proved to be beneficial in suppressing impedance growth when cells were cycled up to and above 4.4 V. 17 Petibon et al 19 • C for at least several weeks without dramatic capacity loss.…”
mentioning
confidence: 99%
“…16 ]O 2 (NMC442)/graphite pouch cells which are balanced for 4.7 V. [16][17][18][19] Ma et al 16 found that NMC442/graphite pouch cells with 2% VC added to 1 M LiPF 6 EC:EMC showed dramatic impedance growth when cycled to 4.3 V and above. The addition of 2% prop-1-ene-1,3-sultone (PES) or 2% PES +1% methylene methanedisulfonate (MMDS) +1% tris(trimethylsilyl) phosphite (TTSPi) ("PES-211") proved to be beneficial in suppressing impedance growth when cells were cycled up to and above 4.4 V. 17 Petibon et al 19 • C for at least several weeks without dramatic capacity loss. Thus, electrolyte additives, concentrated salts and atypical solvents all can play a part in the successful implementation of high voltage Li-ion cells.…”
mentioning
confidence: 99%